Effect of Interface Microstructure on Joint Strength of Zirconia/Titanium Alloy Brazed with Amorphous Zr-Ti-Ni-Cu Active Filler Metal - Sung Woo Park; Hyunjong Lee; Byung Hoon Lee; Tae Hwan Kim; Kyung Il Kim; Se Ah Hong; Minji Kim; Soong-Keun Hyun; Gwan Ho Ryu; Kyung Taek Kim (Metals, 2020)
Active brazing of zirconia with metallic alloys is a promising method for enhancing the mechanical property of zirconia. However, the brazing process of zirconia and metallic alloys has not been studied in detail because of a limitation in selection of materials and processing conditions. Here, we successfully brazed zirconia with Ti-3Al-2.5V alloy using amorphous Zr54Ti22Ni16Cu8 active filler alloy. By manipulating the brazing temperature from 800 °C to 860 °C, a highest strength of ~186 MPa was achieved at 860 °C. Reduced brittle (Zr,Ti)2(Ni,Cu) intermetallic phases from formation of island-type (Zr,Ti) matrix, ZrO2-X, TiO, and TiO2 interlayer play a key role in increasing the joint strength. Our findings will be helpful in developing brazing processes for zirconia and metallic alloys.